Pannexin‐1 channel regulates nuclear content packaging into apoptotic bodies and their size. Issue 13 (19th April 2021) - Phan, Thanh Kha; Fonseka, Pamali; Tixeira, Rochelle; Pathan, Mohashin; Ang, Ching‐Seng; Ozkocak, Dilara Ceyda; Mathivanan, Suresh; Poon, Ivan Ka Ho
Abstract: Apoptotic bodies (ApoBDs), which are large extracellular vesicles exclusively released by apoptotic cells, possess therapeutically exploitable properties including biomolecule loadability and transferability. However, current limited understanding of ApoBD biology has hindered its exploration for clinical use. Particularly, as ApoBD‐accompanying cargoes (e.g., nucleic acids and proteins) have major influence on their functionality, further insights into the mechanism of biomolecule sorting into ApoBDs are critical to unleash their therapeutic potential. Previous studies suggested pannexin 1 (PANX1) channel, a negative regulator of ApoBD biogenesis, can modify synaptic vesicle contents. We also reported that trovafloxacin (a PANX1 inhibitor) increases proportion of ApoBDs containing DNA. Therefore, we sought to define the role of PANX1 in regulating the sorting of nuclear content into ApoBDs. Here, using flow cytometry and label‐free quantitative proteomic analyses, we showed that targeting PANX1 activity during apoptosis, via either pharmacological inhibition or genetic disruption, resulted in enrichment of both DNA and nuclear proteins in ApoBDs that were unexpectedly smaller in size. Our data suggest that PANX1, besides being a key regulator of ApoBD formation, also functions as a negative regulator of nuclear content packaging and modulator of ApoBD size. Together, our findings provide further insights into ApoBD biology and form a novel conceptual framework for ApoBD‐based therapies through pharmacologically manipulating ApoBD contents.